Biodegradable drug-eluting stents: targeting urothelial tumors of upper urinary tract - Barros, Alexandre António Antunes (2016)
Urothelial tumors of upper urinary tract are ranked among the most common types of cancers worldwide. The current standard therapy to prevent recurrence is intravesical Bacillus-Calmetteâ Guerin (BCG) immunotherapy, but it presents several disadvantages such as BCG failure and intolerance. Another way is to use chemotherapy, which is generally better tolerated that BCG. In this case, drugs such as epirubicin, doxorubicin, paclitaxel and gemcitabine are used. Nevertheless, intravesical chemotherapy only prevents recurrence in the short-term.